The Influences of Perceived Usefulness and Perceived Ease of Use of e-HRM on Successfulness of Green HRM Among Employees - Farid, Ridhayati; Raihan, Raihan; Priscilla, Yuddy Giovanna (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Post-COVID-19 pandemic, the hospitality industry faces a major challenge to integrate technologies that support efficiency and sustainability, including the adoption of e-HRM (electronic Human Resource Management) systems in support of Green HRM (GHRM). This study aims to examine the influence of perceived ease of use (PEOU) and perceived usefulness (PU) e-HRM on the successful implementation of GHRM in the four-star hospitality sector in Batam, with attitudes towards use (ATU) as a mediating variable. The research is quantitative with a survey method using a questionnaire of 238 hotel employees who were selected by purposive sampling. The analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results show that PEOU and PU have a significant influence on the success of GHRM, both directly and through ATU. However, PU did not show any significant influence on the ATU. These findings indicate that the perception of ease of use of the system is more important in building a positive attitude than the direct benefits felt. In conclusion, the implementation of e-HRM designed with easy access and intuitive features can strengthen employees' commitment to the company's sustainability initiatives through GHRM.